Public policies of business development and innovation from the perspective of new public management and governance: case CREAME (2014)
The aim of this paper is to analyze public policies of business development and innovation, from the perspective of the new public management, governance and a business incubator that has a large impact on its formulation, CREAME. In themethodology, we used the case study, combining documentary analysis with semi-structured interview. The results evidenced that policies have emerged predominantly in the regional context, by the convergence of different actors, including non governmental, that play an important role in the formulation, implementation and evaluation, which is consistent with the features of the public management model modus vivendi and/or the negotiated of action